Hydrodynamic coefficients of yawed cylinders in open-channel flow. (March 2019) - Persi, Elisabetta; Petaccia, Gabriella; Fenocchi, Andrea; Manenti, Sauro; Ghilardi, Paolo; Sibilla, Stefano
Abstract: The hydrodynamic response of a cylinder in an open-channel flow is experimentally investigated by considering the effects of horizontal orientation and submergence, the latter ranging from fully submerged to half-submerged cases. Drag and side coefficients are measured with a specific hydrodynamic balance which allows the planar rotation and the variation of submergence of the sample. The instrument design and characteristics are discussed, also estimating the uncertainties of force and hydrodynamic coefficients measurement. The tests are carried out under four submergence ratios ( SR, submerged height to water depth), showing that for lower SR the drag and side coefficients increase with respect to tests performed on a fully submerged cylinder, which correspond to the highest SR . The tests performed for a half-submerged cylinder show instead a reduction of the side and drag coefficients, mainly due to the reduced submerged section. The effect of orientation on the two coefficients is different, yet it leads to similar submergence-independent trends. The drag coefficient is maximum for the 90° crossflow configuration, where maximum flow deviation occurs, while the side coefficient is maximum for the 45° orientation, which shows the most asymmetrical flow pattern. Measurements for deep submergence are validated against available literature results, confirming the reliability of the obtained values. Highlights: Measures carried out with a custom-made hydrodynamic balance fit reference data. Drag and side vary with yaw angle proportionally to sample area projection. Cylinders near the water surface have higher coefficients than deeply submerged ones. Half-submerged cylinders present reduced hydrodynamic resistance. Results for half-submerged cylinders are suitable for Large Wood transport models.